Features of immunity by various constellations of principal adaptation hormones and autonomous regulation in practically healthy people - Anatoliy I Gozhenko; Yaroslav L Hrytsak; Liliya G Barylyak; Marta M Kovbasnyuk; Svitlana P Tkachuk; Tetyana A Korolyshyn; Galyna Yo Matiyishyn; Walery Zukow; Igor L. Popovych (Kazimierz Wielki University, 2016)
Gozhenko Anatoliy I, Hrytsak Yaroslav L, Barylyak Liliya G, Kovbasnyuk Marta M, Tkachuk Svitlana P, Korolyshyn Tetyana A, Matiyishyn Galyna Yo, Zukow Walery, Popovych Igor L. Features of immunity by various constellations of principal adaptation hormones and autonomous regulation in practically healthy people. Journal of Education, Health and Sport. 2016;6(10):215-235. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.160979 http://ojs.ukw.edu.pl/index.php/johs/article/view/3936         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 02.10.2016. Accepted: 15.10.2016.       FEATURES OF IMMUNITY BY VARIOUS CONSTELLATIONS OF PRINCIPAL ADAPTATION HORMONES AND AUTONOMOUS REGULATION IN PRACTICALLY HEALTHY PEOPLE   Anatoliy I Gozhenko1, Yaroslav L Hrytsak2, Liliya G Barylyak2,3,4, Marta M Kovbasnyuk4, Svitlana P Tkachuk3, Tetyana A Korolyshyn4, Galyna Yo Matiyishyn3, Walery Zukow5, Igor L Popovych4   1Ukrainian Scientific Research Institute of Transport Medicine Ministry of Health, Odesa   Gozhenko@mail.ru 2Hotel Spa Complex "Karpaty", Truskavets', Ukraine  hrytsak.y@gmail.com 3JSC "Truskavets'kurort", Truskavets', Ukraine   lgbarylyak@biph.kiev.ua 4Laboratory of Experimental Balneology, OO Bogomoletz Institute of Physiology NAS, Kyiv, Ukraine  i.popovych@biph.kiev.ua;   marta.kovbasnyuk@yandex.ua 5Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland  w.zukow@ukw.edu.pl   Abstracts Background. It is known that in practically healthy (without clinical diagnose) people constellations of principal Adaptation Hormones displays widely variability representing different gradations of health and premorbide states. Previously, we found at least four mutually separated groups of people (endocrine clusters). The aim of this study is to elucidate the characteristics of immunity in members of different neuroendocrine clusters. Material and research methods. We determined twice in ten women and ten men aged 33-76 years without clinical diagnose serum levels of Cortisol, Aldosterone, Triiodothyronine, Testosterone and Calcitonin (ELISA) as well as Bayevskiy's Stress Index by HRV as markers of General Adaptation Reactions (GAR). Also used determined by Leukocytogram Popovych's Strain and Adaptation Indices. Immune status evaluated on a set of I and II levels recommended by the WHO. Results. All 40 case was distributed among four neuroendocrine clusters. Cluster N1 contains 10% cases with drastically hypercortisolemia and increased Baevskiy's Stress Index combined with moderately decreased level of Testosterone but normal levels of Triiodothyronine, Aldosterone and Calcitonin. It is accompanied by a significant supression of cellular immunity and insignificant activation of humoral immunity. 12,5% cases (Cluster N2) characterized moderately increased level of Cortisol and Triiodothyronine combined with moderately decreased level of Calcitonin but normal levels of Testosterone and Aldosterone. Despite the normal average level of Stress Index it ranges in a wide range. This is accompanied by negligible inhibition of cellular immunity and significant activation of humoral immunity. 32,5% cases (Cluster N3) characterized moderately increased level of Cortisol too while moderately decreased level of Triiodothyronine as well as Calcitonin and Testosterone combined with upper borderline level of Aldosterone and normal level of Stress Index. This is accompanied by a significant activation of humoral immunity without abnormalities of cellular immunity. In 45% cases (Cluster N4) neuro-hormonal costellation characterized upper borderline levels of Cortisol as well as Testosterone combined with normal levels others hormones and even slightly reduced level of Stress Index. This is accompanied by more pronounced activation of humoral immunity without abnormalities of cellular immunity. Conclusion. Various constellations of Neuroendocrine factors of General Adaptation Reactions accompanied by various constellations parameters of Immunity. Keywords: Cortisol, Aldosterone, Triiodothyronine, Testosterone, Calcitonin, HRV, Immunity, Relationships.